Internalization and Axonal Transport of the HIV Glycoprotein gp120 - Berth, Sarah (ASN Neuro, 2015)
The HIV glycoprotein gp120, a neurotoxic HIV glycoprotein that is overproduced and shed by HIV-infected macrophages, is associated with neurological complications of HIV such as distal sensory polyneuropathy, but interactions of gp120 in the peripheral nervous system remain to be characterized. Here, we demonstrate internalization of extracellular gp120 in a manner partially independent of binding to its coreceptor CXCR4 by F11 neuroblastoma cells and cultured dorsal root ganglion neurons. Immunocytochemical and pharmacological experiments indicate that gp120 does not undergo trafficking through the endolysosomal pathway. Instead, gp120 is mainly internalized through lipid rafts in a cholesterol-dependent manner, with a minor fraction being internalized by fluid phase pinocytosis. Experiments using compartmentalized microfluidic chambers further indicate that, after internalization, endocytosed gp120 selectively undergoes retrograde but not anterograde axonal transport from axons to neuronal cell bodies. Collectively, these studies illuminate mechanisms of gp120 internalization and axonal transport in peripheral nervous system neurons, providing a novel framework for mechanisms for gp120 neurotoxicity.